CURIKULUN AND ITS INNOVATIONS: a comprehensive analysis of its components and developments in the digital era 2024 - Husnilawati, Husnilawati; Pahrudin, Agus; Jatmiko, Agus; Koderi, Koderi (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2025)
The purpose of this study is to thoroughly examine the elements of the curriculum and its development innovations in the context of education in the 2024 digital era. A flexible and inventive curriculum is increasingly needed along with technological advances. Literature content analysis and interviews with education experts and curriculum developers are part of the qualitative methodology used in this study. The results of the study show that the new digital curriculum can increase student engagement and enable more personalized and flexible learning. However, these innovations still face challenges, such as a lack of technological infrastructure and sufficient teacher training. In conclusion, the development of innovative curriculum elements requires strong education policy support and adequate resource allocation. The implications of this study reinforce the theory that the curriculum is not just a static document, but a dynamic system that continues to evolve with the changing times. The integration of digital technology in curriculum development supports constructivism theory and technology-based learning approaches, which allow for a more interactive, personalized, and flexible learning experience. In addition, this research enriches the understanding of how curriculum elements (objectives, content, strategies, evaluation) can be optimized through digital innovation.